2022
DOI: 10.1177/03635465221119186
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Anterior Cruciate Ligament Graft Failure in Professional Athletes: An Analysis of 342 Patients With a Mean Follow-up of 100 Months From the SANTI Study Group

Abstract: Background: Anterior cruciate ligament (ACL) injuries are among the most common knee injuries sustained in elite sport, and athletes generally undergo ACL reconstruction (ACLR) to facilitate their return to sport. ACL graft rupture is a career-threatening event for elite athletes. Purpose/Hypothesis: The purpose of this study was to determine the risk factors for graft failure in professional athletes undergoing ACLR. It was hypothesized that athletes who underwent combined ACLR with a lateral extra-articular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 77 publications
1
19
0
3
Order By: Relevance
“…Fabbriciani et al [10] and Takazawa et al [27] both reported no re‐ruptures, but this may have been due to the small number (12) of cases studied. An 8% re‐rupture rate in rugby was reported by Hopper et al as part of their multisport study [15]. The re‐rupture rate in NFL(6.9% [16] and 18% [25]) and Australian football (30% [20]), which are sports that are comparable to rugby, are similar or higher than those shown in rugby players in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Fabbriciani et al [10] and Takazawa et al [27] both reported no re‐ruptures, but this may have been due to the small number (12) of cases studied. An 8% re‐rupture rate in rugby was reported by Hopper et al as part of their multisport study [15]. The re‐rupture rate in NFL(6.9% [16] and 18% [25]) and Australian football (30% [20]), which are sports that are comparable to rugby, are similar or higher than those shown in rugby players in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Graft re‐rupture is widely reported in studies of elite athletes after primary ACL‐R and ranges between 3 and 19% [2, 9, 11, 14, 15, 19, 20, 24, 25, 29]. Hopper et al [15] in a multi‐sport study found that the re‐rupture rate was not affected by the type of sport played.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by retrospective cohort studies in the literature that compared five‐ and four‐strand autografts and found no significant differences in rupture and instability rates [2, 5, 16]. Failure of ACLR is not only attributed to graft diameter, with medial and lateral meniscus deficiency, non‐anatomic femoral tunnel positioning, and younger patient age all being reported to play a role [14, 27, 28, 34]. In addition, bone morphological risk factors such as increased tibial slope and intercondylar notch stenosis have also been shown to be associated with failure [7, 10, 12, 31].…”
Section: Discussionmentioning
confidence: 69%
“…Firstly, we describe a combined ACL reconstruction and double-bundle ALL reconstruction. 4,7,9,11 Appropriate landmarks are identified and marked including the joint line, Gerdy tubercle, fibular head, and lateral epicondyle. Three stab incisions are made in preparation for the ALL reconstruction.…”
Section: Video Transcriptmentioning
confidence: 99%